Maria Montessori's Pedagogy and its Potential to Promote Peace Education in the Philippines - Kilag, Osias Kit T.; Heyrosa-Malbas, Marsha; Villar, Se P.; Arong, Susan L. (International Journal on Integrated Education, 2023)
This study aims to explore the potential of Montessori's pedagogy in promoting peace education in the Philippines. Using a qualitative research design, the study collected data from 10 participants, including teachers, parents, and Montessori school administrators. The findings of the study suggest that Montessori's approach can contribute to peace education by promoting a child-centered and experiential learning environment, which can foster critical thinking skills and empathy towards others. Moreover, the study identified several challenges to implementing Montessori's pedagogy in the Philippine context, such as the lack of awareness and understanding of the approach among educators and parents, limited availability of trained Montessori teachers, and the lack of resources and support for implementing the approach in schools. The study also proposed strategies for adapting and implementing Montessori's pedagogy in the Philippine context, such as providing training and professional development for teachers, building awareness and understanding of the approach among parents and educators, and developing partnerships and collaborations between Montessori schools and other educational institutions in the Philippines. The study concludes that Montessori's approach has the potential to promote peace education in the Philippines, but more efforts are needed to overcome the challenges and effectively implement the approach in schools.